2(7h-5)=24+9h

Simple and best practice solution for 2(7h-5)=24+9h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7h-5)=24+9h equation:


Simplifying
2(7h + -5) = 24 + 9h

Reorder the terms:
2(-5 + 7h) = 24 + 9h
(-5 * 2 + 7h * 2) = 24 + 9h
(-10 + 14h) = 24 + 9h

Solving
-10 + 14h = 24 + 9h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-9h' to each side of the equation.
-10 + 14h + -9h = 24 + 9h + -9h

Combine like terms: 14h + -9h = 5h
-10 + 5h = 24 + 9h + -9h

Combine like terms: 9h + -9h = 0
-10 + 5h = 24 + 0
-10 + 5h = 24

Add '10' to each side of the equation.
-10 + 10 + 5h = 24 + 10

Combine like terms: -10 + 10 = 0
0 + 5h = 24 + 10
5h = 24 + 10

Combine like terms: 24 + 10 = 34
5h = 34

Divide each side by '5'.
h = 6.8

Simplifying
h = 6.8

See similar equations:

| -2x+19+5x-11= | | 9(x-2)-3=-21 | | Y=z+20 | | 3x+0.5=-8 | | 5x+55=7x+180 | | 4x^2+3x^2=441 | | -9+(-9)=x | | -5=n+2-6 | | 5y=-1-3x | | 5x+3y=30-5x | | -y-y-y-y= | | 2(-16+2x)=x-5 | | 5-4[9-(6y-3)]= | | 3y=5+12 | | 3x+0.5=8 | | N+3=-5+2n+7+4 | | 5x+93+2x=7x+54 | | 4+8(1+6c)=16 | | 6p+9=-9 | | 30-p=p+10 | | 20+p=p+10 | | 3y=-6x+8 | | 24b-22=-4(1-6b) | | 10+p=p+10 | | (4x-6)(4x-5)= | | 3.2y-1.2y=8 | | 100p=p+10 | | -12+5n=21+-6n | | 25p=p+15 | | 4y=-6x+5 | | 25+p=p-15 | | 8x-5=7x+70 |

Equations solver categories